Studi Kasus : Asuhan Keperawatan Pasien Dengan Bersihan Jalan Napas Tidak Efektif Akibat Tuberculosa Paru Di IGD RSD Gunung Jati Kota Cirebon - Sari, Diana; Purbasari, Dwiyanti; Dwi Hikmatun , Khaerunnisa; Komariah , Oom; Fitriyani, Risma (Awatara Publisher, 2024)
Pulmonary tuberculosis is an infectious disease caused by Mycobacterium tuberculosis and attacks the lower respiratory tract. The purpose of this study was to provide nursing care to patients with ineffective airway clearance due to Pulmonary TB in the Emergency Room of Gunung Jati Hospital, Cirebon City with a case study approach. This type of research uses a descriptive case study approach. The sample consisted of one person who experienced an emergency due to a medical diagnosis of Pulmonary Tuberculosis in the Emergency Room of Gunung Jati Hospital, Cirebon City. Data collection was carried out through nursing assessment with anamnesis, physical examination and documentation study. The results of the study showed that the patient was in the green triage, ineffective airway clearance as a priority nursing diagnosis, the patient was given airway management and oxygen 6 npm nasal cannula. Nursing evaluation showed that airway clearance was still ineffective and the patient was treated in the inpatient room. The emergency team needs to carry out complementary therapy in collaborative care for chronic patients.